(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
As a result of the activities developed by the Museum of the Southwest Writing and the ESTELA Project, the corpus of pre-Roman inscriptions in the southwest of Iberia was enriched with some new epigraphic evidence, shortly presented in this paper. These remains do not modify significantly the panorama, but they give rise to some considerations on its most relevant peculiarities and cultural framework. Starting from these new findings and taking into account the most relevant research, with particular emphasis on the fundamental work of Javier de Hoz 2010, this paper exposes some ideas about those epigraphic manifestations. Some well-known monuments and somewhat controversial are revised, pointing alternative interpretations.